ANALISIS PENYAKIT PADA TUMBUHAN HIDROPONIK SELADA MENGGUNAKAN METODE FORWARD CHAINING - Huda, Khoirul Huda Dwi Putra; Arbansyah, Arbansyah; Yulianto, Fendy (Universitas Palangka Raya, 2024)
This research, titled